Genetics and Molecular Diagnostics in Retinoblastoma—An Update. Issue 2 (March 2017) - Soliman, Sameh E.; Racher, Hilary; Zhang, Chengyue; MacDonald, Heather; Gallie, Brenda L.
Abstract : Abstract: : Retinoblastoma is the prototype genetic cancer: in one or both eyes of young children, most retinoblastomas are initiated by biallelic mutation of the retinoblastoma tumor suppressor gene, RB1, in a developing retinal cell. All those with bilateral retinoblastoma have heritable cancer, although 95% have not inherited the RB1 mutation. Nonheritable retinoblastoma is always unilateral, with 98% caused by loss of both RB1 alleles from the tumor, whereas 2% have normal RB1 in tumors initiated by amplification of the MYCN oncogene. Good understanding of retinoblastoma genetics supports optimal care for retinoblastoma children and their families. Retinoblastoma is the first cancer to officially acknowledge the seminal role of genetics in cancer, by incorporating "H" into the eighth edition of cancer staging (2017): those who carry the RB1 cancer‐predisposing gene are H1; those proven to not carry the familial RB1 mutation are H0; and those at unknown risk are HX. We suggest H0* be used for those with residual <1% risk to carry a RB1 mutation due to undetectable mosaicism. Loss of RB1 from a susceptible developing retinal cell initiates the benign precursor, retinoma. Progressive genomic changes result in retinoblastoma, and cancer progression ensues with increasing genomic disarray. Looking forward, novel therapies are anticipated from studies of retinoblastoma and metastatic tumor cells and the second primary cancers that the carriers of RB1 mutations are at high risk to develop. Here, we summarize the concepts of retinoblastoma genetics for ophthalmologists in a question/answer format to assist in the care of patients and their families.